2016
DOI: 10.1111/jopr.12447
|View full text |Cite
|
Sign up to set email alerts
|

Systemic T Cells and Monocyte Characteristics in Patients with Denture Stomatitis

Abstract: Percentages of peripheral lymphocytes, T cells, monocytes, and their subpopulations were similar in both studied groups. The exception was median percentages of CD25+ T cell subsets, which were significantly lower in DS patients than in control subjects. This reduction was observed in both CD4 T cell subset (16.7% and 28.1%; p = 0.0006) and CD8 T cell subset (4.6% and 7.0%; p = 0.007) CONCLUSIONS: While DS and associated local fungal infection do not overtly affect activation of monocytes or lymphocytes, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In addition to reduced saliva flow, poorly-controlled diabetic patients show reduced saliva pH and a reduction of glucose levels, which facilitates oral hypertrophy and colonization [ 20 ]. Numerous studies by Czesnikiewicz-Guzik et al [ 11 , 12 , 13 ] have found that there is a relationship between inflammation in the oral cavity and certain chronic conditions, such as hypertension. The aim of our study was to assess the relationship between the occurrence of systemic diseases with or without a concomitant infection of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reduced saliva flow, poorly-controlled diabetic patients show reduced saliva pH and a reduction of glucose levels, which facilitates oral hypertrophy and colonization [ 20 ]. Numerous studies by Czesnikiewicz-Guzik et al [ 11 , 12 , 13 ] have found that there is a relationship between inflammation in the oral cavity and certain chronic conditions, such as hypertension. The aim of our study was to assess the relationship between the occurrence of systemic diseases with or without a concomitant infection of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical and psychological differences, as well as the coexistence of a number of additional diseases, can make the diagnostics and treatment of edentulism a challenge for both doctors and patients. The study has found that there is also a relationship between inflammation of the oral cavity and certain chronic conditions, such as hypertension [ 11 , 12 , 13 ]. Systemic diseases, such as oral infections, are associated with assignable risks, including atherosclerosis and coronary heart disease, stroke, chronic obstructive pulmonary disease and diabetes and some more.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was found between the two groups. These authors evoke the hypothesis of the limited capacity of patients with dentures and older patients to fight against the infection [ 102 ]. Generally, the process of aging clearly influences several factors in the blood (serum IL-4 and interferon-gamma (IFN-Υ)), independently of the presence or absence of DRCS [ 77 ].…”
Section: Innate Immune Responses and Denture-related Candida Stomatitismentioning
confidence: 99%
“…Risk factors associated with DS are advanced age (Gasparoto, Dionísio, et al., ; Gasparoto, Vieira, et al., ; Gasparoto et al., ; Gasparoto, de Oliveira, Vieira, Porto, Gasparoto, et al., ; Gasparoto, Sipert, et al., ; Gasparoto, de Oliveira, Vieira, Porto, Cunha, et al., ; Pereira et al., ; Zomorodian et al., ); gender (Figueiral et al., ; Gasparoto, Dionísio, et al., ; Gasparoto, Vieira, et al., ; Pereira et al., ; Zomorodian et al., ); host systemic factors related to depressed immune response such as vitamin deficiency, diabetes, and use of immunosuppressors, antibiotics, or drugs with xerostomic side effects and smoking (Altarawneh et al., ; Lyon & de Resende, ; Maciąg et al., ; Shulman et al., ). In addition, local risk factors associated with the dentures, such as poor oral and denture hygiene (Gendreau & Loewy, ; Kulak‐Ozkan et al., ; Webb et al., ), nocturnal and/or continuous denture wear (Altarawneh et al., ; Barbeau et al., ; Bilhan et al., ; Figueiral et al., ; Gendreau & Loewy, ; Shulman et al., ; Webb et al., ; Zomorodian et al., ), poor denture quality (Altarawneh et al., ; Figueiral et al., ; Gendreau & Loewy, ; Webb et al., ), and trauma (Emami et al., ; Figueiral et al., ; Webb et al., ), have all been proposed as predisposing factors.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies that evaluated the production and release of salivary and serum cytokines in DS (Gasparoto, Dionísio, et al., ; Gasparoto, Vieira, et al., ; Gasparoto et al., ; Gasparoto, de Oliveira, Vieira, Porto, Gasparoto, et al., ; Gasparoto, Sipert, et al., ; Gasparoto, de Oliveira, Vieira, Porto, Cunha, et al., ; Leigh, Steele, Wormley, & Fidel, ; Maciąg et al., ; do Nascimento, Pinke, Penitenti, Ikoma, & Lara, ; Peese & Arpornsuwan, ; Pietruski et al., ; Pinke et al., ; Rodriguez‐Archilla, Urquia, Cutando, & Asencio, ; Simunović‐Šoškić et al., ). Cytokines are cell signaling molecules that aid cell‐to‐cell communication in immune responses and stimulate the movement of the cells toward the site of inflammation, infection, and trauma.…”
Section: Introductionmentioning
confidence: 99%